The Global Compact: an analysis of the motivations of adoption in the Spanish context. (21st November 2012) - Arevalo, Jorge A.; Aravind, Deepa; Ayuso, Silvia; Roca, Mercè
<x xml:space="preserve">Abstract</x> In the 10 years after the launch of the United Nations Global Compact (GC), there have been very few empirical assessments of the initiative in the academic literature. In this study, drawing from institutional theory and the resource‐based view of the firm, we examine motivations of business participants to adopt the GC principles in the Spanish context. Using survey data from Spain – the country reporting the highest volume of business participants in the GC – we find that external institutional forces as well as internal organisational resources shape motivations for adopting GC principles. In particular, we find that early and late adopters are motivated similarly by the perceived opportunity of achieving image gains, while late adopters are motivated more by economic gains than early adopters. We further find that regardless of the extent of internal intangible resources possessed, firms are similarly motivated by economic gains. The results also show that companies with more intangible resources are motivated more by image gains than those with fewer resources. Our findings indicate that contrary to its earlier days, economic gains have emerged as an important motivator for the adopters of the GC principles with image gains still being an important motivator.